PENGARUH ZAT PENGATUR TUMBUH ALAMI DARI EKSTRAK TAUGE TERHADAP PERTUMBUHAN PEMBIBITAN BUDCHIP TEBU (Saccharum officinarum L.) VARIETAS BULULAWANG (BL) - Saktiyono Sigit Tri; Rudin Nopiyanto (MEDIAGRO, 2020)
The purpose of this study was to determine the effect of bean sprouts extract as a natural ZPT at various concentrations on the growth of sugarcane seedlings. Variety of sugarcane seedlings used was BL (Bulu Lawang). The parameters observed were plant height (cm), number of leaves (strands), stem diameter (mm), plant wet weight (g) and plant dry weight (g). This research was conducted using a non factorial randomized block design (RBD), consisting of 5 treatments with 3 replications as blocks, so that there were 15 experimental units. Each unit of the experiment contained 3 replications of sample plants, so there were a total of 45 sample plants. The five treatments consist of P0 (Control), P1 (Concentration 20%), P2 (Concentration 40%), P3 (Concentration 60%) and P4 (Concentration 80%). Data were analyzed using analysis of variance (ANOVA) with a significance of 95%, if there were differences followed by Duncan's Multiple Range Test (DMRT). Based on the results of this study indicate that there are significant differences in the parameters of plant height (cm), number of leaves (strands), stem diameter (mm), plant wet weight (g) and plant dry weight (g). Based on research results the effect of soaking bean sprouts extract on the growth of sugar cane seeds showed the best results on P2 treatment (40% concentration). Key Words: Plant Growth Regulator, Sugarcane, Soaking, Nursery